Pierre Chommeliz, faux-monnayeur du désastre, au milieu du XVe siècle - Pierre Prétou (Criminocorpus)
In the middle of the fifteenth century, a letter of pardon forgives Peter Chommeliz for his counterfeiting. Based on the misfortunes inflicted to the man, the letter opens a disastrous reading explaining the crime. Simultaneously, the archive delivers information about criminal networks in late middle ages. Thus, it also outlines the logic of royal repression: by interpreting the crime, the French chancery enhances the majesty of Valois in monetary cases.